The Fengsu-Driven Practice of Sending Infants to China: The Experiences of Chinese Immigrant Mothers in New York - Wong, Kitching Rhoda (2015)
This dissertation explores Fujianese women's transnational parenting experiences. Although transnational mothering is ubiquitous in an era of globalization, this study surfaces the unique aspects of this phenomenon among Chinese female migrants to New York City. These women send months-old infants to China for care expecting their return at school age. The 'satellite-baby' phenomenon (Bohr, 2009) appears unique to Chinese immigrant mothers, particularly those from the Fujian-Fuzhou region. Conducted in the phenomenological tradition of qualitative research, I sought to uncover the complex, contextual experiences mothers experienced in their migration to the US. This included their experiences as immigrants, their decisions to send infants to China, their separation from their babies, and finally, their children's return to New York. This study employed homogeneous and criterion sampling. Informants were immigrant mothers aged 18 to 45 from the Fujian-Fuzhou region of China who spoke Mandarin, who had sent at least one infant for care in China, and whose children had returned to New York within the last six years. Recruited through fliers distributed by key members of the New York City Chinese community, sixteen migrant women participated in semi-structured interviews designed to collect narratives for this study. Two themes dominated study findings. Fengsu, or social customs, norms, and traditions, and mei-banfa, or having no other option, drove informants' decisions beginning with their migration, through employment, marriage, child-bearing, and ultimately the decision to send their infants at three to four months to China. Fengsu-migration led the women to come to the US. Their immigration status and limited English gave them no option (mei-banfa) but to work in subservient jobs. They sent earnings to China to pay migration debts and to support their families. Women had limited social lives in the US, but fengsu expectations that they marry led to xiangqin, or blind dating for husbands. Themes of deskilling and lack of agency predominated. Because of fengsu practice, many informants bore their first child immediately after marriage. As expectant mothers, they knew because of fengsu that their babies would go home to China until they reached school age. Throughout, they struggled with numerous in situ mei-banfa, including huge migration debts, poor living arrangements, and lack of childcare. Consequently, the mothers acted against their own desires to keep their infants in New York and sent them to China where grandparents and others cared for them. This study highlights the effects of this separation of child-absent transnational mothers from their babies. However, for some the experience resulted in renewed agency as women made decisions about subsequent children more consistent with their own aspirations as mothers